Diminished Returns: The Registered Trapline System in Northern Ontario - Finch, David (Ontario History)

(untitled) (The Ontario Historical Society, 2020)
Traplines have come to be regulated by governments which speaks to colonial dispossession and changing values regarding the land, wildlife, and Indigenous peoples. During the fur trade era, Indigenous trappers became decreasingly autonomous economic actors and further declines occurred in the twentieth century as fur trading became marginalized. In the mid-twentieth century, Ontario and other Canadian jurisdictions embarked on a path of increased regulations of game and the assignment of traplines to First Nation harvesters. This article explores the roots and outcomes of the Registered Trapline System in Northern Ontario, and explores how, since the 1940s, a pattern of fluctuating agency is apparent, with shifting degrees of natural resources management that recently has seen some benefits for Indigenous trappers.